Auto-Induction in Oral Esketamine Treatment for Treatment-Resistant Depression: An Exploratory Study - Jolien K. E. Veraart; Cornelis F. Vos; Nieko C. Punt; Dylan Visser; Mireille A. Wessels; Sanne Y. Smith-Apeldoorn; Jeanine Kamphuis; Robert A. Schoevers; Daan J. Touw (Pharmaceuticals)
Background: Esketamine is a rapidly acting antidepressant with robust efficacy in treatment-resistant depression (TRD). Diminishing therapeutic effects and attenuated side effects have been reported after long-term use. This study aimed to investigate its long-term pharmacokinetics and factors that may contribute to reduced efficacy over time in patients with TRD by evaluating the potential role of auto-induction. Methods: Pharmacokinetic data were collected from 18 patients receiving oral esketamine for six weeks. A pharmacokinetic model was developed to predict esketamine and noresketamine plasma concentrations. Observed esketamine and noresketamine plasma concentrations were compared to model-predicted concentrations to assess deviations suggestive of auto-induction. Results: On day 39, plasma concentrations of esketamine and noresketamine were 59% and 35% lower than predicted, respectively, indicative of auto-induction of CYP3A4 and CYP2B6. Conclusions: Auto-induction appears to occur in oral esketamine treatment, which may contribute to reduced therapeutic efficacy and side effects in long-term treatment. Identifying auto-induction as a mechanism of tolerance potentially has important clinical implications. Further studies are warranted to confirm these findings and evaluate strategies to maintain therapeutic efficacy.